The development of lead-less perovskite materials for the photovoltaic application - Chen, Yan (Nanyang Technological University, 2021)
Perovskite solar cells with high efficiency and low fabrication cost have been rapidly developed in response to the pressing demand of the world energy. However, the light absorber materials adopted in the state-of-the-art perovskite solar cells contain the toxic element lead that may pose potential hazards to humans and biological systems. Hence, the discovery and development of new lead-free perovskite materials for the future global commercialization of non-toxic, stable, and efficient perovskite solar cells has become the emerging frontier in photovoltaic research field. In this regards, the thesis here proposed three types of lead-free or lead-less perovskite materials by substituting lead with non-toxic metal elements from the same group as lead in the periodic table (germanium and tin). These model materials were studied through a combination of structural, morphological, optical and electrical characterizations to select the appropriate composition for the application as solar harvesting films in photovoltaic device with measurable performance. In this thesis, according to the predication of computational analysis on the substitute materials for lead-based perovskites in literature, novel germanium(II) and tin(IV) iodide perovskite materials have been successfully synthesized using solution processes and demonstrated desired optical absorption properties for photovoltaic applications. In these two lead-free perovskite systems, various inorganic or small organic cations were utilized in combination with the lead-free metallic cations and iodic anions to selectively tailor the crystal structure, band edge position, and ambient and thermal stabilities of the resulting perovskites. In addition, a lead-less perovskite system with partial tin(II) substitution exemplified the important role of metallic cations in controlling the charge recombination process within perovskite films and at interfaces. In summary, the major findings presented in this thesis dissertation highlight the significance of compositional engineering of the perovskite materials to the fine-tuning of their optoelectronic properties and the performance of their associated devices. Furthermore, this thesis work paves the way for the rational design of eco-friendly, stable, and efficient perovskite materials for photovoltaic applications in future.